Store Atmosphere pada Supermarket Tirta Bangunan Tajur Bogor - Annisa Nabila Putri; Yulianingsih Yulianingsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The physical environment of a retail store plays a strategic role in shaping consumers’ shopping experiences, particularly in brick-and-mortar retail settings. However, empirical studies on store atmosphere in building material retail remain limited, despite its distinctive spatial and functional characteristics. This study aims to describe the implementation of store atmosphere at Tirta Bangunan Tajur Bogor, with a specific focus on store layout as a key element supporting consumer comfort and shopping effectiveness. A descriptive qualitative approach was employed, using field observation, informal interviews with management and employees, participatory involvement in operational activities, and a literature review. The findings reveal that the overall store atmosphere has supported functional shopping activities through adequate lighting, neutral color schemes, and a clean environment. Nevertheless, the store layout requires further adjustment due to increasing product variety and limited display space, which affects customer flow and spatial efficiency. These results indicate that effective layout management plays a central role in enhancing consumer comfort and operational efficiency in building material retail. The study contributes to the literature by highlighting the importance of functional spatial design as part of store atmosphere in non-conventional retail contexts.